Carbon dot modified cement-based material and preparation method thereof
An electrochemical method for preparing carbon dots enhances cement-based materials by promoting uniform hydration and improving compressive strength, addressing the complexity and cost issues of existing methods.
Patent Information
- Application Number
- CN202411142981.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-20
- Publication Date
- 2025-01-03
AI Technical Summary
Current methods for preparing carbon dots for modifying cement-based materials are complex, costly, and not suitable for large-scale production, and there is a lack of efficient and low-cost methods to enhance the mechanical properties of cement using carbon dots.
An electrochemical method is used to prepare carbon dots using electrolytes such as pure water, acetic acid, or polyacrylic acid solutions, which are then incorporated into cement-based materials to enhance hydration and mechanical properties.
The method produces carbon dots with hydrophilic functional groups that promote uniform hydration and improve compressive strength, making it practical for large-scale production with reduced costs.
Smart Images

Figure CN119241141A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cement-based materials, and in particular to a carbon-dot modified cement-based material and a preparation method thereof. Background Art
[0002] Cement is an indispensable material in the construction industry. It is cost-effective and practical. Its excellent mechanical properties and durability make it widely used in the field of modern construction. The mechanical properties of cement-based materials are closely related to their microstructure. Among them, hydration products are an important part of the microstructure. Usually, calcium silicate in cement reacts with water to form calcium silicate hydrate, calcium hydroxide, etc. These hydration products directly affect the mechanical properties of cement-based materials. Therefore, promoting the hydration reaction of cement and improving the structure of hydration products are feasible solutions to improve the mechanical properties of cement.
[0003] Studies have shown that some nanomaterials can promote cement hydration, improve its microstructure, and thus increase its compressive strength. However, the nanomaterials currently used in research are mainly concentrated on nano metal oxides, carbon nanotubes, graphene oxide, nano silicon dioxide, nano calcium carbonate and other materials. Although these materials can indeed significantly improve the performance of cement materials, the preparation of these nanomaterials usually requires the use of ultrasonic treatment, covalent chemical modification or mechanical ball milling to graft oxygen-containing functional groups on their surfaces. These treatments are often complex and costly, and are not suitable for large-scale production.
[0004] Carbon dots are a type of nanomaterial with a particle size of less than 10 nm, consisting of a carbonaceous core and a surface passivation layer rich in functional groups. They have high specific surface area, good dispersibility, and rich surface functional groups. They have shown good application value in high-tech fields such as bioimaging, drug delivery, ion detection, and catalysis. Patent CN114940486 A discloses a method for preparing carbon dots by electrochemical oxidation of carbonized corn cobs. The prepared carbon dots have obvious fluorescent properties and are mainly suitable for the field of bioimaging. The carbon dot output rate is very low.
[0005] At present, there are few studies on the application of carbon dots in cement-based materials and the preparation methods are limited to hydrothermal method and microwave method. Patent CN113683078 A discloses a preparation method of nano-carbon dots and nano-carbon dot concrete that can be used to modify cement-based materials. The microwave hydrothermal reactor is required to have at least two reactors, and the production equipment requires a large investment, which is not conducive to the promotion and application of modified cement-based materials. Therefore, the modification of cement-based materials urgently needs to develop a simple, efficient and low-cost carbon dot preparation method. Summary of the invention
[0006] In view of the above problems, the present invention provides an electrochemical method for preparing carbon dots and its application in modifying cement-based materials. The specific technical solution is as follows:
[0007] A carbon dot-modified cement-based material, characterized in that it includes carbon dots, water, cement and sand, wherein the carbon dots are prepared by an electrochemical method, and the electrolyte used in the electrochemical method is one of pure water, an aqueous solution containing 0.2%-0.5% acetic acid, and an aqueous solution containing 0.2%-0.5% polyacrylic acid.
[0008] In the present application, pure water, an aqueous solution containing 0.2%-0.5% acetic acid, and an aqueous solution containing 0.2%-0.5% polyacrylic acid are electrolyzed to produce hydroxyl groups during the preparation of carbon dots. The prepared carbon dots carry carbon-carbon double bonds and carbon-oxygen double bonds, and therefore contain hydrophilic functional groups such as hydroxyl groups and carboxyl groups. These functional groups are the key to improving the compressive properties of cement-based carbon dots. Among them, the electrolysis time of pure water is relatively long. Adding a small amount of acetic acid or polyacrylic acid to the aqueous solution can improve the electrolysis efficiency and shorten the electrolysis time.
[0009] Preferably, the weight ratio of the carbon dots to cement is 0.05%-0.3%:1.
[0010] A method for preparing a carbon dot-modified cement-based material, comprising:
[0011] Placing the anode and cathode in an electrolyte to electrolyze to obtain a first mixed solution; the electrolyte is one of pure water, an aqueous solution containing 0.2%-0.5% acetic acid, and an aqueous solution containing 0.2%-0.5% polyacrylic acid;
[0012] After the first mixed solution is cooled to room temperature, filtering and purifying to obtain a second mixed solution;
[0013] Concentrating the second mixed solution to obtain a third mixed solution;
[0014] The third mixed solution is frozen until ice forms, and then freeze-dried to obtain carbon dots;
[0015] The carbon dots, water, cement and sand are mixed evenly to obtain a carbon dot-modified cement-based material.
[0016] Preferably, the anode is a graphite rod or a carbonized corn cob, and the cathode is a graphite rod or a platinum wire.
[0017] In this application, the carbonization conditions of corn cobs are N2 as a protective atmosphere, a carbonization temperature of 600°C to 900°C, a heating rate of 5°C / min to 20°C / min, and a carbonization time of 2-5h. Different carbonization conditions will affect the final carbon point size, but will not affect the electrolysis process. The carbon points used in this scheme have no strict requirements on size, and the carbonization conditions of corn cobs can be adjusted according to actual production conditions to reduce costs.
[0018] Preferably, the filtering comprises the following steps:
[0019] Filter paper filtration;
[0020] Filtration through microporous filters;
[0021] Dialysis bag for dialysis.
[0022] Preferably, the size of the micropores in the microporous filter is 0.22 μm.
[0023] Preferably, during dialysis using the dialysis bag, the dialysis time is 48-72 hours, and the molecular weight of the dialysis bag is 500Da to 1000Da.
[0024] Preferably, the method for concentrating the second mixed liquid is rotary evaporation.
[0025] Preferably, the third mixed solution is frozen to a freezing temperature of -20°C, and freeze-dried to obtain powdered carbon dots.
[0026] The beneficial effects of the present invention are:
[0027] First, a solution containing hydrophilic groups such as hydroxyl and carboxyl groups is selected as the electrolyte. The obtained carbon dots have rich oxygen functional groups on the surface, which are easy to form hydrogen bonds with water, so they have excellent water solubility, can make the carbon dots evenly dispersed in water, and increase the contact between the carbon dots and cement particles. The functional groups on the surface of these carbon dots can not only accelerate the dissolution of calcium silicate in cement, promote the hydration of cement and make the hydration products more uniform, but also form covalent chemical connections with calcium silicate hydrates, calcium hydroxide, etc. in the hydration products, reduce the internal load conduction pressure of cement, and thus improve the compressive strength of cement. In addition, due to the presence of long carboxylic acid chains, the carbon dots increase the steric hindrance between cement particles in cement-based materials, improve the compactness of cement-based materials, and enhance the mechanical properties of cement-based materials.
[0028] Second, the raw materials for preparing carbon dots by electrochemical methods are simple and easy to obtain. Compared with the methods for preparing carbon dots in the prior art, this solution has significantly lower requirements for electrodes and electrolytes. Compared with the existing technology for modifying cement-based materials with carbon dots, the electrochemical method used in this solution greatly reduces the investment in production equipment, simplifies the process flow, is highly practical, and has the conditions for large-scale production. In summary, this solution connects the two fields of electrochemical method and cement-based materials with carbon dots as the medium, and obtains a carbon-dot-modified cement-based material that reduces costs and increases efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0031] In the attached figure:
[0032] Figure 1 :Schematic diagram of the experimental device for preparing carbon dots by electrochemical method;
[0033] Figure 2 : The compressive performance test results of carbon dot modified cement-based materials prepared by using graphite rods as cathode and anode and pure water as electrolyte at the 3- and 7-day curing stages;
[0034] Figure 3 : The compressive performance test results of the carbon dot modified cement-based materials prepared by using graphite rods as cathode and anode and 0.2%-0.5% polyacrylic acid solution as electrolyte during the 3 and 7 day curing stages;
[0035] Figure 4 : The compressive performance test results of carbon dot modified cement-based materials prepared by using graphite rod as cathode and carbonized corn cob as anode and 0.2%-0.5% acetic acid solution as electrolyte during the 3 and 7 day curing stages. DETAILED DESCRIPTION
[0036] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Without departing from the spirit and essence of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention all belong to the scope of protection of the present invention. Unless otherwise specified, the experimental materials, reagents, instruments, etc. used in the examples of the present invention are all commercially available; unless otherwise specified, all technical means in the examples of the present invention are conventional means well known to those skilled in the art.
[0037] The present application provides a carbon dot modified cement-based material, comprising carbon dots, water, cement and sand, wherein the carbon dots are prepared by an electrochemical method, and the electrolyte used in the electrochemical method is one of pure water, an aqueous solution containing 0.2%-0.5% acetic acid, and an aqueous solution containing 0.2%-0.5% polyacrylic acid. Specifically, the weight ratio of the carbon dots to cement is 0.05%-0.3%.
[0038] The carbon dots prepared in this example are analyzed by infrared spectroscopy and found to contain a large number of carbon-oxygen double bonds and carbon-carbon double bonds, which means that the carbon dots contain abundant hydrophilic functional groups such as hydroxyl and carboxyl. The carbon dots containing abundant hydrophilic functional groups can firstly promote the contact between water and cement particles, making the cement particles evenly distributed in the solution and producing more uniform hydration products; secondly, the presence of long carboxyl chains enables the carbon dots to enhance the steric hindrance between cement particles and improve the compactness of cement-based materials.
[0039] The present application provides a method for preparing a carbon dot-modified cement-based material, comprising:
[0040] S1: placing the anode and cathode in an electrolyte, and electrolyzing to obtain a first mixed solution; the electrolyte is one of pure water, an aqueous solution containing 0.2%-0.5% acetic acid, and an aqueous solution containing 0.2%-0.5% polyacrylic acid.
[0041] In this step, the anode is a graphite rod or a carbonized corn cob, and the cathode is a graphite rod or a platinum wire; the electrolysis is performed at a rated voltage of 60V for 24-72 hours to obtain a first mixed solution.
[0042] S2: After the first mixed solution is cooled to room temperature, it is filtered to obtain a second mixed solution.
[0043] The filtering in this step specifically includes the following steps:
[0044] S21: filtration with filter paper;
[0045] S22: filtering with a microporous filter; wherein the size of the micropores in the microporous filter is 0.22 μm.
[0046] S23: Dialysis in a dialysis bag, wherein the dialysis time is 48-72 hours, and the molecular weight of the dialysis bag is 500Da-1000Da.
[0047] S3: concentrating the second mixed solution to obtain a third mixed solution.
[0048] In this step, the second mixed liquid can be concentrated by rotary evaporation.
[0049] S4: The third mixed solution is frozen to ice, and then freeze-dried to obtain carbon dots.
[0050] In this step, the third mixed solution is frozen to a freezing temperature of -20°C and freeze-dried to obtain powdered carbon dots.
[0051] S5: Evenly mix the carbon dots, water, cement and sand to obtain a carbon dot-modified cement-based material.
[0052] The specific method for forming the carbon dot modified cement-based material in this step is: completely dissolving the carbon dots in water to obtain a carbon dot solution, adding cement and sand to the carbon dot solution in sequence and stirring at 100 r / min for 120 s, stopping stirring for 90 s, and using a rubber scraper to scrape the mortar on the blades and the pot wall into the middle of the pot within the first 30 s of stopping stirring, and then continuing stirring at 160 r / min for 90 s to obtain the carbon dot modified cement-based material.
[0053] In the electrochemical preparation process of carbon dots in the present application, the anode of the electrode is a dry graphite rod or a carbonized corn cob, and the cathode of the electrode is a graphite rod or a platinum wire. Among them, the carbonization conditions of the corn cob are N2 as a protective atmosphere, the carbonization temperature is 600℃~900℃, the heating rate is 5℃ / min~20℃ / min, and the carbonization time is 2-5h. All electrodes are dried and free of impurities on the surface. The present application uses carbonized corn cobs as anode materials. Carbonized corn cobs have low acquisition costs and abundant resources, which can not only realize the resource recycling of waste, but also reduce the cost of carbon dot preparation.
[0054] Example 1 A carbon dot-modified cement-based material was prepared using graphite rods as cathode and anode and pure water as electrolyte.
[0055] Put the graphite rod into pure water for ultrasonic treatment, remove surface impurities and transfer to an electric constant temperature blast drying oven at 60°C for drying. Insert the dried graphite rod into a beaker equipped with a rotor and 1L pure water, with the distance between the two graphite rods being about 8cm. Turn on the magnetic stirrer for stirring, connect the positive and negative poles of the power supply to the two graphite rods respectively, turn on the power switch, adjust the rated voltage to 60V, and electrolyze for 72h to obtain the first mixed solution.
[0056] The first mixed solution was cooled to room temperature, filtered with filter paper to remove large particles of impurities, and then filtered with a 0.22 μm microporous filter. The obtained filtrate was dialyzed for 24 hours to obtain a second mixed solution.
[0057] The second mixed solution was transferred to a round-bottom flask, and a portion of water was removed by rotary evaporation using a rotary evaporator to obtain a third mixed solution.
[0058] The third mixed solution was placed at -20°C until it froze, and then freeze-dried for 24 hours to obtain carbon dots.
[0059] 0.12g, 0.24g and 0.48g of carbon dots were completely dissolved in 120g of water respectively, 240g of cement and 720g of sand were added to the carbon dot solution in turn and stirred at 100r / min for 120s, then stopped for 90s, and within the first 30s of stopping stirring, the mortar on the blades and the pot wall was scraped into the middle of the pot with a rubber scraper, and then continued to stir at 160r / min for 90s to obtain 0.05%, 0.1% and 0.2% carbon dot modified cement-based materials respectively.
[0060] Example 2: A carbon dot-modified cement-based material is prepared using graphite rods as cathode and anode, and polyacrylic acid solution as electrolyte.
[0061] The graphite rod was placed in pure water for ultrasonic treatment, and after removing surface impurities, it was transferred to an electric constant temperature blast drying oven at 60°C for drying. The dried graphite rod was inserted into a beaker equipped with a rotor and 1L 0.2%-0.5% polyacrylic acid solution. The distance between the two graphite rods was about 8cm. The magnetic stirrer was turned on for stirring. The positive and negative poles of the power supply were connected to the two graphite rods respectively. The power switch was turned on, and the rated voltage was adjusted to 60V. The electrolysis was carried out for 48 hours to obtain the first mixed solution.
[0062] The first mixed solution was cooled to room temperature, filtered with filter paper to remove large particles of impurities, and then filtered with a 0.22 μm microporous filter. The obtained filtrate was dialyzed for 72 hours to obtain a second mixed solution.
[0063] The second mixed solution was transferred to a round-bottom flask, and a portion of water was removed by rotary evaporation using a rotary evaporator to obtain a third mixed solution.
[0064] The third mixed solution is frozen to a freezing temperature of -20°C, and freeze-dried to obtain powdered carbon dots.
[0065] 0.12g, 0.24g, 0.48g and 0.72g of carbon dots were completely dissolved in 120g of water, respectively. 240g of cement and 720g of sand were added to the carbon dot solution in turn and stirred at 100r / min for 120s. Stirring was stopped for 90s, and within the first 30s of stopping stirring, the mortar on the blades and the pot wall was scraped into the middle of the pot with a rubber scraper. Stirring was continued at 160r / min for 90s to obtain 0.05%, 0.1%, 0.2% and 0.3% carbon dot modified cement-based materials, respectively.
[0066] Example 3: A carbon dot-modified cement-based material was prepared using graphite rods as cathodes and carbonized corn cobs as anodes and acetic acid as electrolyte.
[0067] Place a graphite rod in pure water and perform ultrasonic treatment to remove surface impurities. Carbonize a corn cob in N2 at 600-800°C for 2-5 hours and then rinse off impurities. Transfer the carbonized corn cob and graphite rod to an electric constant temperature blast drying oven at 60°C for drying. Insert the dried electrode into a beaker equipped with a rotor and 1L 0.2%-0.5% acetic acid solution with a distance of about 8cm between the two electrodes. Turn on the magnetic stirrer for stirring. Turn on the power switch, adjust the rated voltage to 60V, and electrolyze for 24 hours to obtain a first mixed solution.
[0068] The first mixed solution was cooled to room temperature, filtered with filter paper to remove large particles of impurities, and then filtered with a 0.22 μm microporous filter. The obtained filtrate was dialyzed for 48 hours to obtain a second mixed solution.
[0069] The second mixed solution was transferred to a round-bottom flask, and a portion of water was removed by rotary evaporation using a rotary evaporator to obtain a third mixed solution.
[0070] The third mixed solution was placed at -20°C until it froze, and then frozen for 24 hours and dried to obtain carbon dots.
[0071] 0.12g, 0.24g and 0.48g of carbon dots were completely dissolved in 120g of water respectively, 240g of cement and 720g of sand were added to the carbon dot solution in turn and stirred at 100r / min for 120s, then stopped for 90s, and within the first 30s of stopping stirring, the mortar on the blades and the pot wall was scraped into the middle of the pot with a rubber scraper, and then continued to stir at 160r / min for 90s to obtain 0.05%, 0.1% and 0.2% carbon dot modified cement-based materials respectively.
[0072] Comparative Example
[0073] Add 240g of cement and 720g of sand into 120g of water in turn and stir at 100r / min for 120s, stop stirring for 90s, and use a rubber scraper to scrape the mortar on the blades and the pot wall into the middle of the pot within the first 30s of stopping stirring, and continue stirring at 160r / min for 90s to obtain ordinary cement-based material.
[0074] Experimental Example 1
[0075] The cement-based materials with different carbon dot ratios obtained in Example 1 and the comparative example were placed in a 40mm×40mm×40mm mold, and the mold was removed after molding under natural conditions for 1 day. After demoulding, the specimens were placed in a constant temperature and humidity standard curing box with a temperature of 20±1°C and a humidity of more than 95% for 3 days and 7 days for compression test. Each group of experiments was repeated 3 times, and the average values were taken for comparison. The results are shown in the following table:
[0076] Example 1 The compression test results of the carbon dot cement-based composite material prepared by using graphite rods as cathode and anode respectively and pure water as electrolyte.
[0077] Table 1 Compression test results of carbon-dot cement-based composites in Example 1
[0078]
[0079] The compression test results of the carbon dot cement-based composite material in Example 1 are shown in Tables 1 and Figure 2As shown, under the same preparation environment, the compressive strength of ordinary cement-based materials (carbon dot content is 0) is 28Mpa after 3 days of curing, and the compressive strength after 7 days of curing is 33.6Mpa. When 0.05% of carbon dots are added to the cement-based materials to prepare modified cement-based materials, the compressive strength after 3 days of curing is 30.4Mpa, which is 8.57% higher than that of ordinary cement-based materials; when 0.1% of carbon dots are added to the cement-based materials to prepare modified cement-based materials, the compressive strength after 3 days of curing is 32Mpa, and the compressive strength after 7 days of curing is 37.6Mpa, which is 14.29% and 11.9% higher than that of ordinary cement-based materials, respectively. The experimental results show that adding at least 0.05% of the carbon dots to cement-based materials can improve the early compressive properties of cement-based materials, and adding at least 0.1% of the carbon dots to cement-based materials can significantly improve the compressive strength of cement-based materials.
[0080] Example 1: Pure water is used as the electrolyte. Pure water contains abundant hydroxyl groups, which are very easy to form hydrogen bonds, and can increase the interaction between carbon dot molecules, thereby enhancing the stability of carbon dots. At the same time, hydroxyl groups have good water solubility and high chemical activity. During the electrolysis process, functional groups such as hydroxyl groups can react with other functional groups on the surface of carbon dots or ions in the electrolyte. This reaction mechanism promotes the grafting of other functional groups such as hydroxyl groups on carbon dots. Due to the grafting of these functional groups, carbon dots are combined with other matrix materials, thereby enhancing the application potential of carbon dots.
[0081] The infrared spectrum analysis of the carbon dots prepared in this embodiment shows that they contain a large number of carbon-oxygen double bonds, carbon-carbon double bonds and oxygen-hydrogen bonds, which means that the carbon dots are rich in hydrophilic functional groups such as hydroxyl and carboxyl groups. The carbon dots rich in hydrophilic functional groups can firstly promote the contact between water and cement particles, so that the cement particles are evenly distributed in the solution, and produce more uniform hydration products. Secondly, the carbon dots rich in hydrophilic functional groups can also enhance the steric hindrance between cement particles and improve the compactness of cement-based materials.
[0082] Experimental Example 2
[0083] The cement-based materials with different carbon dot ratios obtained in Example 2 and the comparative example were placed in a 40mm×40mm×40mm mold, and the mold was removed after molding under natural conditions for 1 day. After demolding, the specimens were placed in a constant temperature and humidity standard curing box with a temperature of 20±1°C and a humidity of more than 95% for 3 days. After 7 days, the compression test was performed. Each group of experiments was repeated 3 times, and the average value was taken for comparison. The results are shown in the following table:
[0084] Example 2 The compression test results of the carbon dot cement-based composite material prepared by using graphite rods as cathode and anode respectively and 0.2%-0.5% polyacrylic acid solution as electrolyte.
[0085] Table 2 Compression test results of carbon-dot cement-based composites in Example 1
[0086]
[0087] The compression test results of the carbon dot cement-based composite material in Example 2 are shown in Table 2 and Figure 3 As shown, under the same preparation environment, the compressive strength of ordinary cement-based materials (carbon dot content is 0) is 24.7Mpa after 3 days of curing, and the compressive strength after 7 days of curing is 32.2Mpa. When 0.05% of carbon dots are added to the cement-based materials to prepare modified cement-based materials, the compressive strength after 3 days of curing is 27.6Mpa, which is 11.74% higher than that of ordinary cement-based materials; when 0.3% of carbon dots are added to the cement-based materials to prepare modified cement-based materials, the compressive strength after 3 days of curing is 27.4Mpa, and the compressive strength after 7 days of curing is 36.5Mpa, which is 10.93% and 13.35% higher than that of ordinary cement-based materials, respectively. The experimental results show that adding at least 0.05% of the carbon dots to cement-based materials can improve the early compressive properties of cement-based materials, and adding at least 0.3% of the carbon dots to cement-based materials can significantly improve the compressive strength of cement-based materials.
[0088] Example 2 uses polyacrylic acid solution as the electrolyte. The polyacrylic acid solution contains abundant long carboxyl chains. Carboxyl groups are hydrophilic functional groups, so they are very easy to form hydrogen bonds, which can increase the interaction between carbon dot molecules, thereby enhancing the stability of carbon dots. In addition to excellent water solubility, carboxyl groups also have high chemical activity. During the electrolysis process, they can react with other functional groups on the surface of carbon dots or ions in the electrolyte. This reaction mechanism promotes its grafting on carbon dots. Due to the grafting of these functional groups, carbon dots are combined with other matrix materials, thereby enhancing the application potential of carbon dots.
[0089] The infrared spectrum analysis of the carbon dots prepared in this embodiment shows that they contain a large number of carbon-oxygen double bonds, carbon-carbon double bonds and oxygen-hydrogen bonds, which means that the carbon dots are rich in hydrophilic functional groups such as hydroxyl and carboxyl groups. The carbon dots rich in hydrophilic functional groups can firstly promote the contact between water and cement particles, so that the cement particles are evenly distributed in the solution, and produce more uniform hydration products. Secondly, the carbon dots rich in hydrophilic functional groups containing long carboxylic acid chains can also enhance the steric hindrance between cement particles and improve the compactness of cement-based materials.
[0090] Experimental Example 3
[0091] The cement-based materials with different carbon dot ratios obtained in Example 3 and the comparative example were placed in a 40mm×40mm×40mm mold, and the mold was removed after molding under natural conditions for 1 day. After demolding, the specimens were placed in a constant temperature and humidity standard curing box with a temperature of 20±1°C and a humidity of more than 95% for 3 days. After 7 days, the compression test was performed. Each group of experiments was repeated 3 times, and the average value was taken for comparison. The results are shown in the following table:
[0092] Example 3: Compression test results of carbon dot cement-based composites prepared using graphite rods as cathodes, carbonized corn cobs as anodes, and 0.2%-0.5% acetic acid solution as electrolyte
[0093] Table 3 Compression test results of carbon-dot cement-based composites in Example 3
[0094]
[0095] The compression test results of the carbon dot cement-based composite material in Example 3 are shown in Table 3 and Figure 4 As shown, under the same preparation environment, the compressive strength of ordinary cement-based materials after curing for 3 days is 26.1Mpa, and the compressive strength after curing for 7 days is 33.6Mpa. When 0.2% of carbon dots are added to the cement-based materials to prepare modified cement-based materials, the compressive strength after curing for 3 days is 29.7Mpa, which is 13.79% higher than that of ordinary cement-based materials; when 0.1% of carbon dots are added to the cement-based materials to prepare modified cement-based materials, the compressive strength after curing for 3 days is 27.2Mpa, and the compressive strength after curing for 7 days is 37.6Mpa, which is 4.21% and 11.9% higher than that of ordinary cement-based materials, respectively. The experimental results show that adding at least 0.2% of the carbon dots to cement-based materials can improve the early compressive properties of cement-based materials, and adding at least 0.1% of the carbon dots to cement-based materials can significantly improve the compressive strength of cement-based materials.
[0096] Example 2 uses acetic acid solution as the electrolyte. Acetic acid solution contains abundant hydroxyl, carboxyl and methyl functional groups. These hydrophilic functional groups are very easy to form hydrogen bonds, which can increase the interaction between carbon dot molecules, thereby enhancing the stability of carbon dots. At the same time, hydroxyl, carboxyl and the like have good water solubility and high chemical activity. During the electrolysis process, oxygen-containing functional groups such as hydroxyl and carboxyl can react with other functional groups on the surface of carbon dots or ions in the electrolyte. This reaction mechanism promotes the grafting of hydroxyl, carboxyl and other functional groups on carbon dots. Due to the grafting of these functional groups, carbon dots are combined with other matrix materials, thereby enhancing the application potential of carbon dots.
[0097] The infrared spectrum analysis of the carbon dots prepared in this embodiment shows that they contain a large amount of carbon-oxygen double bonds, carbon-oxygen single bonds, carbon-carbon double bonds and oxygen-hydrogen bonds, which means that the carbon dots contain abundant hydrophilic functional groups such as hydroxyl groups and carboxyl groups. The carbon dots containing abundant hydrophilic functional groups can firstly promote the contact between water and cement particles, so that the cement particles are evenly distributed in the solution, and produce more uniform hydration products. Secondly, the carbon dots containing abundant hydrophilic functional groups can also enhance the steric hindrance between cement particles and improve the compactness of cement-based materials.
[0098] Based on the above experimental results, the carbon dots obtained by electrolysis of pure water, polyacrylic acid, and acetic acid can significantly improve the mechanical properties of cement-based materials by adding 0.1%-0.3% during the cement preparation process. Among them, the carbon dots prepared with pure water as the electrolyte have the most significant effect on improving the compressive performance, but the electrolysis time of pure water as the electrolyte is relatively long; adding a small amount of polyacrylic acid and acetic acid can accelerate the electrolysis reaction, and the compressive performance of the obtained carbon dot-modified cement-based materials is also improved. In actual production, the production efficiency and product quality can be weighed according to different needs, and the appropriate electrolyte and electrode materials can be selected. This solution has strong practical applicability and a wide range of choices. The modified cement-based materials prepared are more widely used than ordinary cement-based materials.
[0099] It can be understood that the above embodiments only express the preferred implementation modes of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the patent scope of the present invention. It should be pointed out that, for ordinary technicians in this field, the above technical features can be freely combined without departing from the concept of the present invention, and several deformations and improvements can be made, which all belong to the protection scope of the present invention. Therefore, all equivalent changes and modifications made to the scope of the claims of the present invention should belong to the coverage of the claims of the present invention.
Claims
1. A carbon dot modified cement-based material, characterized in that: The invention comprises carbon dots, water, cement and sand, wherein the carbon dots are prepared by an electrochemical method, and the electrolyte used in the electrochemical method is one of pure water, an aqueous solution containing 0.2%-0.5% acetic acid, and an aqueous solution containing 0.2%-0.5% polyacrylic acid.
2. A carbon dot modified cement-based material according to claim 1, characterized in that: The weight ratio of the carbon dots to cement is 0.05%-0.3%.
3. A method for preparing a carbon dot-modified cement-based material, characterized in that: include: Placing the anode and cathode in an electrolyte to electrolyze to obtain a first mixed solution; the electrolyte is one of pure water, an aqueous solution containing 0.2%-0.5% acetic acid, and an aqueous solution containing 0.2%-0.5% polyacrylic acid; After the first mixed solution is cooled to room temperature, filtering and purifying to obtain a second mixed solution; Concentrating the second mixed solution to obtain a third mixed solution; The third mixed solution is frozen until ice forms, and then freeze-dried to obtain carbon dots; The carbon dots, water, cement and sand are mixed evenly to obtain a carbon dot-modified cement-based material.
4. The method for preparing a carbon dot-modified cement-based material according to claim 3, characterized in that: The anode is a graphite rod or a carbonized corn cob, and the cathode is a graphite rod or a platinum wire.
5. The method for preparing a carbon dot-modified cement-based material according to claim 3, characterized in that: The filtration and purification comprises the following steps: Filter paper filtration; Filtration through microporous filters; Dialysis bag for dialysis.
6. The method for preparing a carbon dot-modified cement-based material according to claim 5, characterized in that: The size of the micropores in the microporous filter is 0.22 μm.
7. The method for preparing a carbon dot-modified cement-based material according to claim 5, characterized in that: When the dialysis bag is used for dialysis, the dialysis time is 48-72 hours, and the molecular weight of the dialysis bag is 500Da-1000Da.
8. The method for preparing a carbon dot-modified cement-based material according to claim 3, characterized in that: The method for concentrating the second mixed liquid is rotary evaporation.
9. The method for preparing a carbon dot-modified cement-based material according to claim 3, characterized in that: The third mixed solution is frozen to a freezing temperature of -20°C, and freeze-dried to obtain powdered carbon dots.
